Systematic Literatur Review: The Impact of Urban Heat Is-Land (Uhi) On Air Quality - Asfiya, Najmi; Indah, Fitri Permata (Journal of Climate Change Society, 2024)
The Urban Heat Island (UHI) phenomenon causes an increase in temperature in urban areas, significantly impacting air quality and public health. This study aims to identify the causes of UHI, its effects on air quality, and to assess vegetation-based solutions for its mitigation. The method used includes a systematic literature review of 30 relevant articles on the impact of UHI on air quality, particularly its effects on human health. Data sources include articles published between 2019-2024 that are relevant to the study and have been cited more than 100 times. The results show that UHI can increase temperatures in urban areas by 5-10°C, worsen air quality by raising ozone concentrations, and affect public health, particularly among vulnerable groups. Tree planting and expanding green areas have been shown to effectively reduce temperatures by up to 3°C. The conclusion highlights that UHI mitigation through greening is an essential step to improve air quality and public health in urban environments. Policies supporting tree planting and the development of green open spaces are crucial for creating healthier and more sustainable cities